La pervivencia del estoicismo senequista en las paremias españolas - Pascual-López, Xavier (Rzym a Półwysep Iberyjski: Inspiracje i powiązania na przestrzeni dziejów, 2021)
The Stoic doctrine of Seneca was assimilated in the Middle Ages and in the Renaissance by Christianity and Humanism, which made it one of the basic references of ancient culture. In addition, in the Spanish sphere it was adopted as an anachronistic reference of Hispanicness. Both factors favoured the wide diffusion of his works at the time in which the Spanish proverbs were forged. The aim of this chapter is to trace Seneca’s reception in Spanish proverbs, especially those regarding self-control, how to deal with the vicissitudes of fortune, the capacity for moral improvement, and how virtue is the key to achieving happiness.